POTENSI PROBIOTIK BAKTERI ASAM LAKTAT ASAL BEKASAM IKAN NILA - Astri Nurnaafi; Iriani Setyaningsih; Desniar - (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
Bekasam is well known in Indonesia as one of fermented fish product. Several fermented products generate lactic acid bacteria (LAB) which has probiotic potential with beneficial effects on human health. However, In Indonesia, the research on LAB isolated from fermented fish product, including bekasam, is still rarely conducted. The aim of this study was to evaluate the probiotic potential of LAB isolated from bekasam. Two LAB isolates namely NS(5) and NS(6) were selected based on their resistance to gastric pH (pH 2.0), intestinal pH (pH 7.2) and bile salts (0.5% oxgal). Pathogenic test, antimicrobial activity test, characterization and identification of the isolats were also performed respectively. The result showed that NS(5) isolate survived at pH 2.0, pH 7.2 and bile salts (oxgal). It was obtained that NS(5) isolate was non pathogenic bacteria which exhibited antimicrobial activity against Salmonella Typhimurium ATCC 14028 and Escherichia coli. The characterization result showed that NS(5) isolate was Gram-positive bacteria, rod-shaped, non-endospore producer, negative catalase, homofermentative, non motile, having an amilolitik as well as lipolitik activity and able to grow at 30-37°C, NaCl 2-7% dan pH 4.4-9.6. Isolate NS(5) isolate was then identified as Lactobacillus plantarum 1 strain with 99.9% of similarity. Meanwhile, NS(6) isolate was not able to survive in the medium containing bile salts (oxgal), therefore it was not categorized as a probiotic candidate.